PENGARUH PEMBERIAN JUS TOMAT TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS TELAGA - Hamna Vonny Lasanuddin; Fadli Syamsuddin; Guswinda Diu (Institut Nalanda, 2023)
Hypertension is widely suffered in various countries, especially in Indonesia. The treatment of grade I and grade II hypertension patients is nonpharmacological treatment, by improving a healthy lifestyle which starts with eating foods namely tomatoes. The purpose of this study was to determine the effect of giving tomato juice on reducing blood pressure in hypertension sufferers in the Telaga Puskesmas Working Area. The research design used the Pre-Experimental Pre-Post Test research method with a total sample of 15 people taken using a sampling technique, namely purposive sampling. The results showed that the average value of systolic blood pressure before giving tomato juice was 146.67 mmHg and the average diastolic blood pressure was 91.33 mmHg and the average systolic blood pressure after giving tomato juice was 131 mmHg and diastolic blood pressure was 84.33 mmHg. The results of the Wilcoxon test before and after the intervention of tomato juice showed that systolic and diastolic blood pressure in the intervention group were obtained respectively p value in the systolic variable = 0.003 (p ≤ α 0.05), and the p value in the diastolic variable = 0.000 (p ≤ α 0.05). Consumption of tomato juice is effective in lowering blood pressure both systolic and diastolic in people with hypertension.